Exchange rates and information about future fundamentals. (October 2022) - Gholampour, Vahid
Highlights: The paper quantifies the effect of future macro fundamentals on exchange rates. Exchange rate informativeness is defined as the contribution of future fundamentals to the variance of the adjusted exchange rate. Future macro fundamentals account for 0.11 of the variance of exchange rates. Abstract: Asset prices reflect aggregate private information of agents about future macroeconomic fundamentals. This paper uses a dispersed information model as the theoretical framework and empirically measures the informativeness of exchange rates for traditional macroeconomic variables. Exchange rate movements are related to observed macro fundamental shocks, future fundamentals, and aggregate noise shocks. The measure of informativeness is defined as the contribution of future fundamentals to the variance of the adjusted exchange rate, which is a function of future fundamental shocks and noise trade. Baseline results show that future fundamentals account for 11 percent of the variance of adjusted exchange rates.